Integration of Point‐of‐Care Ultrasound Education Into the Internal Medicine Core Clerkship Experience. (2nd April 2021) - Lambrecht, Jason E.; Zhang, Kang; Tierney, David M.; Millner, Paul; Giovannini, David; Barron, Keith; Novak, William; Patel, Sanjay A.; Dversdal, Renee; Cox, Emily J.; LoPresti, Charles M.
Abstract : Point‐of‐care ultrasound (POCUS) is becoming an essential skill for internists. To date, there are no professional guidelines for how POCUS skills should be taught to medical students. A panel of POCUS experts from seven academic medical centers in the United States was convened to describe the components of independently developed IM clerkship POCUS training programs, identify areas of similarity and difference, and propose recommendations for alignment.